Pengaruh Work-Family Conflict, Selfefficacy dan Faktor Demografik Terhadap Burnout - Aulia Anisyah Fassa; Miftahuddin Miftahuddin (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2015)
Burnout is psychological symptom on individuals who do withdrawal from his work which happen due to inability of individuals to respond to demand. This psychological symptom marked with three main aspects, those are emotional exhaustion, depersonalization and declined self-achievement. Objective of this study is to examine the effect of work-family conflict, self-efficacy and demographic factor on burnout. Sample of tis study is 293 teachers of one of private school in Jakarta. Measurement tool used in this study is a adaptation of Maslach Burnout Inventory (MBI), work-family conflict constructed by Carlson, Kamar, and Williams, and General Self-Efficacy Sherer (GSESH). Confirmatory Factor Analysis used to test Instrument Validity. Data analysis technique using Multiple Regression Analysis. The result of this study indicates that there is a significant effect of work-family conflict (time-based conflict, Starin-based conflict, behavior-based conflict) on burnout, whereas burnout isn't affected by self-efficacy and demographic factor.